Reva N. S. The status of the title in the printed advertisement based on the English discourse - Reva N. S. (Philological Treatises, 2020)
This article in question deals with headline as information marker in terms of English media discourse. The types of headlines are being classified; their polyfunctionality in ad texts is being analyzed.